Mixed Convection Heat Transfer of Al2O3-H2O Nanofluid in a Trapezoidal Lid-driven Cavity at Different Angles of Inclination (Texas Journal of Engineering and Technology, 2022)
Mixed convection in a trapezoidal lid driven cavity containing a heat source circular cylinder using two fluids separately